ELECTRONIC NOTIFICATION SYSTEM AND WITH JUDICIAL PRODUCTIVITY IN THE SUPERIOR COURT OF JUSTICE OF CAJAMARCA - Idrogo Zamora, Lic. Abel (2022)
The purpose of determining the existingrelationship between the electronic notification system and judicial productivity in the Superior Court of Justice of Cajamarca throughout the pandemic year of 2020 has been achieved by the electronic notification system. Basic research, quantitative research approach as well as descriptive correlational methods were used. The population comprises 150 collaborators with a sample of 109 workers from different working areas. The analysis shows both the email and web page notification have a significance of 0,000<0,05, confirming their direct relationship. To conclude, it wouldbe advisable that the Information Technology office of the Superior Court of Justice of Cajamarca through the District Administrative Management invest in the ongoing technological equipment improvement so as to have better judicial productivity indicators along with a standing training to the judicial integrated system personnel and collaborators.